The effects of partisan party politics in local authorities: a case of Harare city council (2000-2016) - Nyanhongo, Aaron S. (Midlands State University, 2018)
The year 2000 marked the rise of a formidable opposition political party MDC to challenge ZANU PF monopoly in the Harare city council as a result subsequent years becomes theatre for a humiliating electoral defeat of ZANU PF. Harare City Council was turned into a political battle field as ZANU PF intensified partisan politics in the Administration of the local authorities to survive the democratic storm using all means at their disposable which has led to the detriment of the City Council. In trying to identify the effects of partisan party politics in Harare City Council the researcher used qualitative and quantitative methods to solicit information from respondents with questionnaires and interviews as the instruments of research. From the findings of the research ,partisan party politics has negatively affected HCC in a multiplicity of ways which includes maladministration, demise of good governance, deterioration of service delivery, urban anarchy and disorderly ,grave financial loses just to mention a few. This research has prescribe recommendation to mitigate and curtail a plethora of effects that has been inflicted in the Harare city council by partisan party politics which are de-politicization of the Harare City council, Harmonization of all the acts governing local Authorities with the new constitution, and also to nurture a culture of good corporate governance through strict moral ethics among other issues.